The role of personal and job resources for telework's affective and behavioral outcomes - Junça Silva, A.; Violante, C.; Brito, S. (Kybernetes, 2024)
Purpose: Recently new forms of telework emerged, such as the hybrid model; however, little is known about how and when it promotes performance. Based on the job-demands-and-resource model, we developed a conceptual framework to demonstrate that the hybrid model of telework positively influences performance via positive affect. Furthermore, we identified both personal (emotional intelligence) and job resources (autonomy) as moderators of this relationship. Design: To test the proposed model, we collected data from teleworkers who were in a hybrid telework regime from the telecommunications industry (N=290). Findings: The results showed that (1) telework positively influenced positive affect and, in turn, performance; (2) the indirect effect of telework on performance through positive affect was moderated by both emotional intelligence and autonomy. Originality: These results appear to be fundamental for a better conceptual and practical understanding of how and when hybrid telework can improve performance.